2017
DOI: 10.1186/s12870-017-1045-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of markers for selecting higher oil content in oil palm

Abstract: BackgroundOil palm (Elaeis guineensis, Jacq.) is the most important source of edible oil. The improvement of oil yield is currently slow in conventional breeding programs due to long generation intervals. Marker-assisted selection (MAS) has the potential to accelerate genetic improvement. To identify DNA markers associated with oil content traits for MAS, we performed quantitative trait loci (QTL) mapping using genotyping by sequencing (GBS) in a breeding population derived from a cross between Deli Dura and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 44 publications
0
25
0
3
Order By: Relevance
“…The first SNP discovery in oil palm using ddRAD-seq with Pst I- Msp I was conducted with 3417 informative SNPs 9 . In a later study 32 , 2139 informative SNPs were identified using ddRAD-seq with Pst I- Msp I in an oil palm breeding population, and a high-density SNP genotyping array was developed 40 . In this study, we discovered more than 10,000 informative SNPs using a different approach: single digest RAD-seq with the Pst I 35 , modified for a highly heterozygous breeding oil palm population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first SNP discovery in oil palm using ddRAD-seq with Pst I- Msp I was conducted with 3417 informative SNPs 9 . In a later study 32 , 2139 informative SNPs were identified using ddRAD-seq with Pst I- Msp I in an oil palm breeding population, and a high-density SNP genotyping array was developed 40 . In this study, we discovered more than 10,000 informative SNPs using a different approach: single digest RAD-seq with the Pst I 35 , modified for a highly heterozygous breeding oil palm population.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has successfully been applied to discover thousands of markers in plants such as wheat and barley 26 , sorghum 27 , rice 28 , switchgrass 29 , sesame 30 , and in insects and fish 31 . While more than ten genetic linkage maps are available for oil palm, only two linkage maps was based on around 1000 SNPs 9 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…SNPs detected by GBS have allowed the genetic dissection of genotypic variation in complex traits in many plant species [34][35][36]. Specifically, in oil palm the GBS technique has been used for identifying candidate genes related to oil bunch [37], bunch weight [20,37], stem height [21] and oil quality traits studies [38] with the enzymes ApeKI and PstI-MspI. Here, we used the enzyme PstI for the library construction, allowing us to identify relatively high number of SNPs with probably novel genetics variants, which according to Chung et al [39] is one of the most important advantages of…”
Section: Association Analysismentioning
confidence: 99%
“…For example, QTL analyses have been conducted for the traits of bunch number, fresh fruit bunch yield, oil yield, oil to bunch content and fatty acid composition 15 20 and leaf area 21 . With the advent of next-generation sequencing (NGS) and genotyping by sequencing (GBS), genome-wide association studies (GWAS) have been used to identify the oil yield-related loci 22 24 . A GWAS for oil to dry mesocarp content (O/DM) on 2,045 Tenera palms was performed using 200 K SNPs and identified 80 loci which were significantly associated with O/DM 23 .…”
Section: Introductionmentioning
confidence: 99%